Informal Economy in Russia: A Brief Overview - БарсуковаСветлана Юрьевна; РадаевВадим Валерьевич (Journal of Economic Sociology, 2012)
The review is devoted to sociological studies in the field of informal and shadow economy in Russia. It discusses the rise of the shadow economy in the Post-Soviet era, involving transition from fictitious and virtual economy to shadow dealings, from relationships of «blat» to business networking, and from pilfering to tax evasion. Moreover, it addresses the institutionalised practices of corruption and use of violence in business, the maintenance of inter-family reciprocal exchanges and the progressive legalization of business activities. The brief overview proposes key findings concerning the differences between the informal sectors of the Soviet and Post-Soviet periods and the main trends of the modern development in Russian shadow economy.